Political Theory of Societal Association: Case of the Failed State Of Syria—Part 5 Brexit - Betz, Frederick (Advances in Social Sciences Research Journal, 2021)
In this fifth paper of a series on failing states, we analyze the impact that the large numbers of Syrian refugees from the Syrian civil war (2010-2019) had on political association in Britain – triggering a major change British policy and possibly threatening national unity. The theoretical model of political association is composed of three dimensions in the political dichotomies of: (1) ‘kinship or reciprocal-altruism’, (2) ‘centralization or decentralization-of-power’, and (3) ‘idealism or realism;. This is a cross-disciplinary political theory which can apply to different societies and to different times in a society.